Mechanical alloying synthesis and investigation of the structural and magnetic properties of nanostructured Fe60Al35Zn5 alloy - Berdjane, D.; Hafs, T.; Hafs, A.; Ayaz, R. (SPRINGER HEIDELBERG, 2025)
Conventional synthesis routes for Fe-Al-Zn alloys often face challenges such as elemental segregation and limited control over microstructural refinement, which hinder their functional performance. To overcome these issues, this study employs high-energy ball milling to promote solid-state alloying and nanostructuring in Fe60Al35Zn5 (wt.%) powders, systematically examining the influence of milling duration (0-36 h) on their structural and magnetic evolution. Structural analysis by X-ray diffraction, refined using the Rietveld method with the MAUD software, revealed the progressive formation of an Fe (Al, Zn) solid solution after 12 h of milling. Prolonged treatment (36 h) induced significant microstructural refinement, as reflected by an increase in the lattice parameter to 0.287 nm, a reduction of crystallite size to nearly 16 nm, and the development of microstrains around 1.12%. Magnetic characterization, carried out by vibrating sample magnetometry, highlighted the strong correlation between milling-induced nanostructuring and the magnetic response. The variation of saturation magnetization, coercivity, and remanence with milling duration demonstrated that mechanical alloying not only promotes solid solution formation but also tailors the alloy's magnetic properties through microstructural control.
Keywords: Powder; Mechanical alloying; Microstructure; X-Ray Diffraction (XRD); Magnetic Properties; Ferromagnetic; AL-FE; PHASE-TRANSFORMATION; IRON ALUMINIDES; POWDERS; EVOLUTION; NI; CO; EQUILIBRIA; STABILITY; Materials Science